Pendampingan pengelolaan sekolah lansia menuju lansia sehat dan mandiri - Sukesi, Tri Wahyuni; Mulasari, Surahma Asti; Sulistyawati, Sulistyawati; Erviana, Vera Yuli (Universitas Ahmad Dahlan, 2025)
The elderly, defined as individuals aged 60 and above, often face challenges related to health, social, and economic factors that affect their quality of life. Programs such as Senior Schools and Senior Learning Spaces aim to support the physical, social, and mental health of the elderly through relevant educational activities. However, management and facility challenges required attention. The goal of this research was to enhance the management capacity of Senior Learning Spaces through training for partners in developing elderly learning programs and improving learning infrastructure. This research used a qualitative approach with Focus Group Discussions (FGD) and curriculum workshops at the Senior School of Yayasan Senior Madani Indonesia, Social Club Indonesia, from November 5-10, 2024. The study involved 10 informants and aimed to design a curriculum relevant to the needs of the elderly. The outcome of this reasearch was a structured curriculum for senior schools, covering areas such as worship, health, Quran reading, and simple technology. This curriculum was relevant to the needs of the elderly and supported the goal of fostering healthy, independent, and productive seniors.